1986
DOI: 10.1172/jci112338
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the defect underlying the lysosomal storage of sialic acid in Salla disease. Lysosomal accumulation of sialic acid formed from N-acetyl-mannosamine or derived from low density lipoprotein in cultured mutant fibroblasts.

Abstract: IntroductionSalla disease is a lysosomal storage disorder characterized by mental retardation and disturbed sialic acid metabolism. To study the metabolism of extracellular sialic acid, lowdensity lipoprotein (LDL) was labeled in the sialic acid moiety (periodate-NaB3H4) or in the protein moiety (125I). Binding, interialization, lysosomal degradation, and exit of products of protein catabolism were similar in normal and mutant fibroblasts. Upon incubation with LDL labeled in the sialic acid moiety, mutant cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…[3H]NANA bound to low-density lipoprotein (LDL) was taken up normally by the lysosomes of Salla disease fibroblasts but was cleared at a much slower rate than in normal cells (6). In these studies the specific radioactivity of the labeled free NANA was diluted by large amounts of nonradioactive NANA present in the Salla cells but not in the normal cells.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[3H]NANA bound to low-density lipoprotein (LDL) was taken up normally by the lysosomes of Salla disease fibroblasts but was cleared at a much slower rate than in normal cells (6). In these studies the specific radioactivity of the labeled free NANA was diluted by large amounts of nonradioactive NANA present in the Salla cells but not in the normal cells.…”
mentioning
confidence: 98%
“…Normal fibroblasts exposed to ManNAc yielded granular fractions with up to 88 pmol of NANA per unit of hexosaminidase (no exposure: 2 pmol per unit of hexosaminidase); Salla disease cells exposed to 30 mM ManNAc produced granular fractions that had acquired up to 496 pmol of NANA per unit of hexosaminidase more than the endogenous level offree NANA in the granular fractions (see Table 1). Since lysosomes accumulate NANA in Salla disease (5,6), this suggested that the lysosomes within the granular fractions were being loaded by the ManNAc exposure. Substantial amounts of free NANA were found in other compartments of the normal cells but were removed during isolation of the lysosome-rich fractions.…”
mentioning
confidence: 99%
“…The results led to the conclusion that NANA is released from the lysosomes in mutant cells at a slower rate than from control cells (Renlund et al, 1986a). Although SD occurs predominantly in Finland, sporadic cases from other countries have been reported.…”
Section: Salla Diseasementioning
confidence: 95%
“…It should be pointed out that most degradative processes, which have been classically attributed to lysosomes, can proceed in late endosomes (5). Hence, it is not surprising that the capacity of SASD fibroblasts to degrade internalized macromolecules is not significantly affected by the unique phenotype of their lysosomes (66).…”
Section: Figmentioning
confidence: 99%